RETROPERITONEAL PARAGANGLIOMA: BRIEF LITERATURE REVIEW AND CASE REPORT - A.D. GAIBOV; O. NEMATZODA; F.S. SHOEV; Z.V. GOIBOVA; U.M. AVGONOV (Avicenna Tajik State Medical University, 2019)
The article presents a summary of historical data about prevalence, pathogenesis, diagnostic difficulties and possible treatment options for retroperitoneal paraganglioma. A special place is given to modern research methods in identifying and refining the genesis of tumour. The clinical example shows possible errors in both clinical and topical diagnostics. The need for preoperative preparation using selective α2 -blockers is justified. The tumour is removed from the middle-middle laparotomy access with a good result against the background of stabilization of the condition and normalization of the basic parameters of homeostasis. Histological research showed a mixed version of tumor structure with no elements of malignization.